The Effect of Litter Size Relative to Functional Teat Count on Lactating Sow and Litter Performance - Abigail K. Jenkins; Sierra M. Collier; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Kyle F. Coble; Paul Corns (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 1,005 mixed-parity sows (Line 1050, PIC) and their litters were used to evaluate the effect of litter size relative to functional teat count on lactating sow and litter performance. Sows were blocked by parity category (P1, P2-P4, and P5+) and functional teat count determined at the time of farrowing and then allotted to one of four treatments. There were 251 or 252 sows per treatment. Treatments consisted of one fewer piglet than functional teats (-1), the same number of pigs as functional teats (0), one more pig than functional teats (+1), or two more pigs than functional teats (+2). Cross-fostering occurred within 24 h of farrowing. Pigs were individually weighed after cross-fostering and the afternoon before weaning. All pigs born weighing less than 2 lb were cross-fostered onto sows that were not included in this study. Sow body weight (BW), caliper score, and backfat measurements were collected at the time of entry (approximately d 112 of gestation) and weaning. Parity category, treatment, and their interaction, as well as teat category (≤ 13, 14-15, and ≥ 16 teats) were included in the model as fixed effects. Any fall-behind piglets, agreed upon by research and farm staff, were recorded and removed from the sow, and no replacement piglet was added to that litter. As litter size relative to functional teat count increased, sows lost more weight and caliper units (linear, P ≤ 0.005). However, the sow culling rate due to failure to conceive decreased (linear, P = 0.038). Litter size and litter weight increased (linear, P < 0.001) as litter size relative to functional teat count increased at both d 2 and weaning. However, litter ADG was greatest for -1 and +2 sows compared to 0 and +1 sows (quadratic, P = 0.045). Mean piglet BW at weaning (linear, P < 0.001) and piglet ADG decreased (quadratic, P = 0.042) as litter size relative to functional teat count increased. On-test (d 2 to wean) removals and mortality increased (linear, P < 0.001) as litter size relative to functional teat count increased. Wean-to-estrus interval was longer for sows with the same number of pigs as functional teats (P < 0.05) compared to +2 sows with -1 and +1 sows intermediate. Even though piglet removals and mortality were greater as the number of pigs relative to teat count increased, pigs weaned per sow per year (PSY) increased as litter size relative to functional teat count increased (linear, P < 0.001). In conclusion, the optimal litter size relative to teat count is dependent on criteria selected. To achieve the lowest piglet mortality and sow BW loss, and highest piglet weaning weight, sows should have one less pig than functional teats after cross-fostering. However, for the highest number of pigs weaned per litter and PSY, sows should have two more pigs than functional teats after cross-fostering.
Keywords: functional teat count; lactating sow; litter size